2018
DOI: 10.3390/pharmaceutics10030076
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene/SBE-β-CD Inclusion Complexes Formulated into Nanoparticles with Chitosan to Overcome the Absorption Barrier for Bioavailability Enhancement

Abstract: Raloxifene (RXF) is a hormone-like medication used for treating postmenopausal osteoporosis and estrogen-dependent breast cancer, yet associated with bad low bioavailability due to poor solubility. This study was intended to develop cyclodextrin/chitosan nanoparticles (ccNPs) for oral delivery of RXF in order to enhance the oral bioavailability. RXF-loaded ccNPs (RXF-ccNPs) were prepared by cyclodextrin inclusion followed by complexation with chitosan. RXF-ccNPs were fully characterized by particle size, morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…RLX has been reported to stimulate gene promoters regulated by ERβ subtype that guards against tumor formation in response to estrogen; therefore, it exhibits anti-tumor activity in breast cancer cells [ 6 ]. Nevertheless, RLX suffers from poor aqueous solubility and exposure to dramatic pre-systemic metabolism that lead to diminished bioavailability that does not surpass 2% [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…RLX has been reported to stimulate gene promoters regulated by ERβ subtype that guards against tumor formation in response to estrogen; therefore, it exhibits anti-tumor activity in breast cancer cells [ 6 ]. Nevertheless, RLX suffers from poor aqueous solubility and exposure to dramatic pre-systemic metabolism that lead to diminished bioavailability that does not surpass 2% [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of enhancing RLX bioavailability, Wang et al [ 84 ] reported the formulation of RLX inclusion complex using sulfo-butyl-ether-β-cyclodextrin followed by conjugation to chitosan to form RLX-loaded cyclodextrin/chitosan nanoparticles (RLX-ccNPs). The enhancement of oral bioavailability of RLX-ccNPs relative to RLX suspensions was about 3.60-fold.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of simultaneously exploiting the advantages of both CD and nano-lipid carriers by joining them in a unique drug delivery system, by loading the drug-CD system into the lipid nanoparticles, has recently been reported [32,33,34,35]. In particular, loading into SLN of HCT as HPβCD binary system rather than as plain drug allowed to enhance the entrapment efficiency from 57% up to 66%, to prolong the formulation stability at 4 °C from 1 to 3 months, and to improve the drug release, with an almost 3-times increase of the released amount after 6 h [21].…”
Section: Introductionmentioning
confidence: 99%